Dual emission tunable in the near-infrared (NIR) and visible (VIS) spectral range by mix-LnMOF. Issue 39 (21st September 2015) - de Jesus, Roberta Anjos; da Luz, Leonis Lourenço; Santos, Danilo Oliveira; Costa, José Arnaldo Santana; Navickiene, Sandro; Gatto, Claudia Cristina; Júnior, Severino Alves; de Mesquita, Maria Eliane
Abstract : In this study, we describe the synthetic approach, crystallographic structure, luminescent behavior in heteronuclear coordination polymers with emission in the visible (Eu 3+ and organic ligand) and near-infrared (Nd 3+ ) range. Abstract : In this study, we describe the synthetic approach, crystallographic structure, luminescent behavior and elucidation of the channels of the energy conversion in heteronuclear coordination polymers with emission in the visible (Eu 3+ and organic ligand) and near-infrared (Nd 3+ ) range. The [(Nd0.9 Eu0.1 )2 (dipc)3 (H2 O)3 ] n · n H2 O, [(Nd0.7 Eu0.3 )2 (dipc)3 (H2 O)3 ] n · n H2 O, [(Nd0.5 Eu0.5 )2 (dipc)3 (H2 O)3 ] n · n H2 O, [(Nd0.3 Eu0.7 )2 (dipc)3 (H2 O)3 ] n · n H2 O, [(Nd0.1 Eu0.9 )2 (dipc)3 (H2 O)3 ] n · n H2 O, [Eu2 (dipc)3 (H2 O)3 ] n · n H2 O and [Nd2 (dipc)3 (H2 O)3 ] n · n H2 O materials are obtained by hydrothermal conditions from pyridine-2, 6-dicarboxylic acid (H2 dipc) and Ln2 O3 oxide (Ln = Eu and Nd). The fine structures in the emission spectrum and spectral profile are used to investigate the ion responsible for the emission characteristics of a material (6 ), based on coordination polyhedron. The heteronuclear systems show emission in the dual spectral range (NIR-VIS) tuned for blue or red. The tuning of emission on the red (Eu 3+ ) or blue (organic ligand) range may be performed by controlling the stoichiometric ratio of the lanthanide ions and by controlling the excitation wavelength. Nd 3+ ions display self-absorption of emission to dipc ligand, resulting in interference on the emission band profile ranging from 400 to 600 nm. The energetic process of energy transfer is operated by a cascade of energy transfer, from dipc ligand mainly to Eu 3+ ions and finishing on the Nd 3+ ion. The efficient sensitization to Nd 3+ by Eu 3+ ions is due to the presence of many resonant energy levels and the short distance between these ions.